A linear graphene edge nanoelectrode1. Issue 42 (25th May 2015) - Li, Kai; Jiang, Jingyun; Dong, Zelin; Luo, Hongxia; Qu, Liangti
<x xml:space="preserve">Abstract</x> A nanometer-thick linear graphene edge nanoelectrode is constructed based on the edge plane of chemical vapor deposition (CVD) grown graphene, which shows much better electrochemical performance compared with traditional carbon fibre microelectrodes.